Wizualizacja skutków finansowych jako metoda oceny projektu - Jakubczyc, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The VoFI or Visualisation of Financial Implications method has been discussed. It has been tried to explain if there is any reasonable connection between visualisation and graphics. Though the conclusion is not optimistic, it has been shown that the VoFI method is an interesting device and should be applied in the practice of project appraisals.
Keywords: project appraisal; VoFI method